Exploratory Analysis of the Economically Justifiable Price of a Hypothetical RSV Vaccine for Older Adults in the Netherlands and the United Kingdom. (15th September 2021) - Zeevat, F; Luttjeboer, J; Paulissen, J H J; van der Schans, J; Beutels, P; Boersma, C; Postma, M J; ,
Abstract: Background: In older adults, the burden of respiratory syncytial virus (RSV) resembles that of influenza and may even be considered worse due to the lack of preventive interventions. This study was performed to identify the available literature on RSV infection in older adults, and to provide updated exploratory results of the cost-effectiveness of a hypothetical RSV vaccine in the Netherlands and the United Kingdom. Methods: A literature search was performed in Medline and EMBASE on 11 November 2019, which served as input for a static decision-tree model that was used to estimate the EJP, for an RSV vaccine applying different willingness-to-pay (WTP) thresholds. WTP thresholds applied were €20 000 and €50 000 per quality-adjusted life-year for the Netherlands, and £20 000 and £30 000 per quality-adjusted life-year for the United Kingdom. Analyses were—in line with country-specific guidelines—conducted from a societal perspective for the Netherlands and a third-party payer perspective for the United Kingdom. The robustness of the cost-effectiveness results was tested in sensitivity analysis. Results: After screening the literature, 3 studies for the Netherlands and 6 for the United Kingdom remained to populate the country-specific models. In the base case analysis for the Netherlands (mean RSV incidence, 3.32%), justifiable vaccine prices of €16.38 and €50.03 were found, based on applying the lower and higher WTP thresholds, respectively. Similarly, for the United Kingdom (mean incidence, 7.13%), vaccine prices of £72.29 and £109.74 were found, respectively. Conclusion: RSV vaccination may well be cost-effective in both the Netherlands and the United Kingdom, depending on the exact RSV incidence, vaccine effectiveness and price. However, sensitivity analysis showed that the results were robust based on varying the different parameter estimates and assumptions. With RSV vaccines reaching the final stages of development, a strong need exists for cost-effectiveness studies to understand economically justifiable pricing of the vaccine.